Effect of iron-fortified jamun leather on the Asunra-induced anemia in Sprague Dawley rats - Naz, Nosheen; Khan, Moazzam Rafiq; Shabbir, Muhammad Asim; Faisal, Muhammad Naeem (Frontiers in Nutrition, 2023)
Micronutrients such as minerals and vitamins are required in a minute quantity but play a pivotal role in the functioning of the body. Therefore, deficiency in one of them can lead to lethal health conditions. Iron deficiency anaemia is one of the most common micronutrient deficiencies across the world and is affecting women and children. The present study aimed to investigate the anti-anaemic effect of fortified jamun leather on anaemia biomarkers and haematology in anaemic female Sprague Dawley rats. A total of 40 Sprague Dawley rats were used in 4 groups. Iron deficiency anaemia was induced by oral administration of the Asunra drug. The treatments were fed at two dosage levels i.e., 40 and 60% iron-fortified leather. All animals were treated for 60 days and the parameters including biochemical, and histopathology of the kidney and liver were examined. The experiment’s findings showed that the group fed with iron-fortified leather (G3) succeeded significantly (P<0.05) in restoring the serum iron (98.68±2.88 µg/dL), haemoglobin (12.41±0.32 g/dL)), ferritin (24.54±1.98 ng/mL) and haematocrit levels (39.30±1.66%) at the end of the 60 days period. Additionally, the treated group’s mean values for transferrin and total iron binding capacity were lower than those of the anaemic rats, indicating an improvement in iron levels. The microscopic analysis revealed that treatments had no toxic effects on the kidney and liver tissues, except in the diseased group, which had necrosis and irregular cell structure. It was concluded that iron-fortified jamun leather helped improve iron deficiency biomarkers and imparted a non-toxic effect on tissues in rats.